Cauchy Extension of Mα-Integral and Absolute Mα-Integrability - Garces, Ian June L (Archīum Ateneo, 2015)
Park, Ryu, and Lee recently introduced a Henstock-type integral, which lies between the Mcshane and the Henstock integrals. This paper proves the closure property of this new integral under Cauchy extension, and presents a characterization on absolute Mα-integrability